Essentials of intellectual property : law, economics, and strategy - Poltorak, Alexander (Alexander I.); Lerner, Paul (Paul J.) (Hoboken, N.J. : Wiley, 2011)
"The definitive primer on intellectual property for business professionals, non-IP attorneys, entrepreneures, and inventors Full of valuable tips, techniques, illustrative real-world examples, exhibits, and best practices, the Second Edition of this handy and concise paperback will help you stay up to date on the newest thinking, strategies, developments, and caselaw in intellectual property. Presents fundamentals of patents, trademarks, copyrights, trade secrets and other less-know forms of IP, such as registered design and mask works Covers important concepts such as IP strategy, protection, audits, valuation, management, and competitive intelligence Offers an introduction to IP licensing and enforcement Now features discussion of critical precedent-setting recent IP cases and proposed patent reform Providing business professionals and IP owners with in-depth knowledge of this extremely important subject, this book helps those new to this field gain a better understanding and appreciation for the results of their creative abilities."--
The big three : patents, trademarks, and copyrights -- The supporting players : other types of IP : trade secrets and know-how, mask works, and noncompetition and nondisclosure agreements -- Protecting the fruits of your research and development -- Know what you have (IP audit) and what the other guy has (competitive intelligence) -- What is it worth? Putting a value on intellectual property -- Make more money by sharing (licensing) -- Corporate officers and directors beware : you can be liable for mismanaging intellectual property -- Enforcing your rights -- The fundamental things apply, as time goes by : intellectual property in cyberspace -- The patent portfolio and its effect on stock price -- How the courts have changed the patent law -- Patent reform.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Intellectual property -- United States; z; LAW -- Intellectual Property -- General; LAW -- Administrative Law & Regulatory Practice; Intellectual property; United States